2020
DOI: 10.4103/ijcm.ijcm_593_20
|View full text |Cite
|
Sign up to set email alerts
|

Initial viral load of a COVID-19-infected case indicated by its cycle threshold value of polymerase chain reaction could be used as a predictor of its transmissibility - An experience from Gujarat, India

Abstract: Background: Transmission dynamics of the infectious disease Corona Virus Disease - 19 (COVID-19) is yet to be understood fully. The study aimed at exploring whether quantitative viral load of COVID-19-infected case indicated by cycle threshold (Ct) value of real-time reverse transcription polymerase chain reaction could predict about transmission pattern in the community. Materials and Methods: An observational study was conducted involving 1976 individuals, suspected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Recently, one public health research institute based in Ahmedabad had established and suggested a public health control strategy of COVID-19 infections based on their pilot research work. [ 4 5 ] The strategy stresses upon the rationality that, the viral load could be an important determinant in spreading infections in the community. Individuals with high viral load are super-spreaders - they take the centre stage in person to person transmissions of coronavirus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, one public health research institute based in Ahmedabad had established and suggested a public health control strategy of COVID-19 infections based on their pilot research work. [ 4 5 ] The strategy stresses upon the rationality that, the viral load could be an important determinant in spreading infections in the community. Individuals with high viral load are super-spreaders - they take the centre stage in person to person transmissions of coronavirus.…”
Section: Methodsmentioning
confidence: 99%
“…But cases started declining visibly following implementation of viral load/Ct-based segregation and management following adoption of it by Government of Gujarat as per suggestion of ICMR-National Institute of Occupational Health on experimental basis. [ 5 ] It may be noted that it was restricted to Ahmedabad district only initially to assess its impact. There was a plan to implement it all over Gujarat state if proved to be effective.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that only 7% of the infected ones carried high viral load, while another 9% of the infected population had moderate viral load and rest 84% were carrying low viral loads as per community distribution was concerned. [19] Viral load was categorised as high when cycle threshold value = <24, moderate = 24 to <31 and low = 31 & above (Figure 1).…”
Section: Recent Experience From Indiamentioning
confidence: 99%
“…Further, the results might be extended to emphasise the need for sterilising such fomite surfaces to prevent viral transmission. Considering the positive relation between viral load and the disease contagiousness [19,23,24], the sources (spreader/positive subjects) with high viral load should be treated with great care, i.e., health care facility with possibly high viral load should adopt maximum precautionary measures. The study indicates that fomites could play an important role in the disease transmission in addition to human contact, particularly at COVID-19 care facilities, market places etc.…”
Section: Recent Experience From Indiamentioning
confidence: 99%